Temporal trends and racial/ethnic- and sex-differences in LDL cholesterol control among US adults with self-reported atherosclerotic cardiovascular disease - Danh Q. Nguyen; Neil Keshvani; Alvin Chandra; Pamela L. Alebna; Dave L. Dixon; Michael D. Shapiro; Erin D. Michos; Laurence S. Sperling; Ambarish Pandey; Anurag Mehta (Elsevier, 2024)
Objective: Current guidelines for secondary prevention of atherosclerotic cardiovascular disease (ASCVD) recommend targeting a low-density lipoprotein cholesterol (LDL-C) of < 70 mg/dL. However, temporal trends and racial/ethnic- and sex-differences in achievement of LDL-C targets are not well described. We assessed trends and racial/ethnic- and sex-differences in achievement of LDL-C < 70 mg/dL using data from the National Health and Nutrition Examination Survey (NHANES) from 2005 to 2008 to 2017-March 2020. Methods: We combined NHANES cycles into 4 periods: 2005-2008, 2009-2012, 2013-2016, and 2017-March 2020 and included participants ≥ 40 years with self-reported ASCVD. We estimated LDL-C < 70 mg/dL prevalence over time and further stratified by sex and race/ethnicity. We used multivariable logistic regression adjusted for social determinants of health and clinical covariates to model LDL-C target attainment. Results: Among 1,826 NHANES participants representing 7,161,221 US adults with self-reported ASCVD (59.6% ≥ 65 years, 56.4% male, 74.8% White), LDL-C target attainment increased from 19.0% (95% CI, 15.3%-23.3%) in 2005-2008 to 26.3% (95% CI, 20.4%-33.1%) in 2017-March 2020 (P = 0.012 for trend). Achievement of LDL-C < 70 mg/dL significantly rose among men from19.5% (95% CI, 15.1%-24.8%) to 29.4% (95% CI, 20.7%-29.9%) without significant change in women (from 18.3% [95% CI, 13.6%-24.2%] to 22.5% [95% CI, 13.0%-35.9%]; P = 0.241 for trend). Improvement in LDL-C target attainment was similar among White, Black, and Hispanic individuals (∼5-7% increase) and was greatest among individuals of other (non-White, Hispanic, or Black) race/ethnicity (23.1% increase). In our multivariable analysis, comorbid diabetes and ages 65-75 and > 75 years were associated with LDL-C target attainment. Conclusion: LDL-C control modestly improved between 2005 and 2008 and 2017-March 2020; however, only ∼1/4 of individuals met guideline-directed LDL-C treatment targets by 2017-March 2020. Women had lower LDL-C control and lesser magnitude of improvement in LDL-C control than men, highlighting a need for targeted interventions to improve lipid-lowering therapy utilization in this population.